Анализ состояния заземляющих устройств действующих энергообъектов Украины - Колиушко, Денис Георгиевич; Руденко, Сергей Сергеевич; Колиушко, Георгий Михайлович (НТУ "ХПИ", 2017)
В работе проведен анализ нормируемых параметров заземляющих устройств (ЗУ) энергообъектов Украины, находящихся в эксплуатации. Создана база данных результатов диагностики состояния ЗУ действующих энергообъектов. Получены статистические распределения превышения допустимых значений напряжения прикосновения, напряжения на ЗУ и сопротивления ЗУ для подстанций различных классов напряжения. Обоснована необходимость выполнения реконструкции ЗУ в соответствии с требованиями к допустимому значению напряжения прикосновения.

The diagnostics was performed for grounding grids more than 1 000 existing power plants. In this paper the standardized parameters grounding of the power plants, which are in operation in Ukraine, were analyzed. To solve this problem we compiled the statistical base of standardized parameters, we performed the analysis for the the statistical distributions of exceeding allowable value of the touch voltage, grounding voltage and grounding resistance for substations of different voltage classes. The necessity performing of grounding reconstruction in accordance with the requirements for allowable value of the touch voltage was substantiated.
Analysis state of grounding grids of existing power plants of Ukraine
Keywords: ЗУ; напряжение прикосновения; сопротивление; статистическое распределение; горизонтальный заземлитель; электромагнитная диагностика